Bacterial diversity of autotrophic enriched cultures from remote, glacial Antarctic, Alpine and Andean aerosol, snow and soil samples - E. González-Toril; R. Amils; R. J. Delmas; J.-R. Petit; J. Komárek; J. Elster (Copernicus Publications, 2009)
Four different communities and one culture of autotrophic microbial assemblages were obtained by incubation of samples collected from high elevation snow in the Alps (Mt. Blanc area) and the Andes (Nevado Illimani summit, Bolivia), from Antarctic aerosol (French station Dumont d'Urville) and a maritime Antarctic soil (King George Island, South Shetlands, Uruguay Station Artigas), in a minimal mineral (oligotrophic) media. Molecular analysis of more than 200 16S rRNA gene sequences showed that all cultured cells belong to the Bacteria domain. Phylogenetic comparison with the currently available rDNA database allowed sequences belonging to Proteobacteria Alpha-, Beta- and Gamma-proteobacteria ), Actinobacteria and Bacteroidetes phyla to be identified. The Andes snow culture was the richest in bacterial diversity (eight microorganisms identified) and the marine Antarctic soil the poorest (only one). Snow samples from Col du Midi (Alps) and the Andes shared the highest number of identified microorganisms ( Agrobacterium , Limnobacter , Aquiflexus and two uncultured Alphaproteobacteria clones). These two sampling sites also shared four sequences with the Antarctic aerosol sample ( Limnobacter , Pseudonocardia and an uncultured Alphaproteobacteria clone). The only microorganism identified in the Antarctica soil ( Brevundimonas sp.) was also detected in the Antarctic aerosol. Most of the identified microorganisms had been detected previously in cold environments, marine sediments soils and rocks. Air current dispersal is the best model to explain the presence of very specific microorganisms, like those identified in this work, in environments very distant and very different from each other.